014 The diagnostic odyssey for fabry disease: ten years experience in testing. Issue 6 (24th May 2018) - Dobbins, Julia; Fuller, Maria; Pyragius, Tim; Brion, Kristian; Chin, Sharon; Gurner, Melissa; Pacyna, Janina; Stark, Samantha; Fletcher, Janice M
Abstract : Introduction: Fabry disease is an X-linked disorder of glycosphingolipid metabolism arising from a deficiency of the enzyme, α-galactosidase A (AGA). In the absence of a family history, biochemical diagnosis is conferred by reduced activity in dried filter paper blood spots (DBS), elevations in globotriaosylsphingosine (lyso-Gb3) and/or identification of a mutation within the GLA gene. Methods: From 2008 to 2012, AGA determinations were performed on leucocytes and in 2012, DBS testing was introduced. A mass spectrometric method to quantify lyso-Gb3 in plasma was added to our repertoire of testing in 2016. Mutation analysis was performed using either Sanger or Next Generation Sequencing, the latter confirmed by sequencing. Results: Between 2008 and 2012, approximately 1000 samples were screened for Fabry disease using AGA determinations in leucocytes and 29 patients were confirmed positive (diagnosis rate of 2.9%). Since 2012, approximately 4000 samples have been screened from DBS, with 126 patients being confirmed positive (diagnosis rate of 3.2%). There were 24 patients with AGA deficiency and a GLA gene variant which did not have elevated lyso-Gb3 (approximately 20% of positives). Discussion: Fabry disease is a relatively complicated disease to diagnose and requires significant interpretation of results from all three tests. As an X-linked disease, classically affected males are easier to identify, but females are more difficult to diagnose as their DBS can be normal, even when symptomatic. Further testing via lyso-Gb3 and mutation analysis is required to make a final biochemical diagnosis. The ease of submitting a DBS for testing has contributed to an increase in test requests.